Clostridium geopurificans Strain MJ1 sp nov., A Strictly Anaerobic Bacterium that Grows via Fermentation and Reduces the Cyclic Nitramine Explosive Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) - Kwon, Man Jae; Wei, Na; Millerick, Kayleigh; Popovic, Jovan; Finneran, Kevin (SPRINGER, 2014)
A fermentative, non-spore forming, motile, rod-shaped bacterium, designated strain MJ1(T), was isolated from an RDX contaminated aquifer at a live-fire training site in Northwest NJ, United States. On the basis of 16S rRNA gene sequencing and DNA base composition, strain MJ1(T) was assigned to the Firmicutes. The DNA G+C content was 42.8 mol%. Fermentative growth was supported by glucose and citrate in a defined basal medium. The bacterium is a strict anaerobe that grows between at pH 6.0 and pH 8.0 and 18 and 37 A degrees C. The culture did not grow with hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) as the electron acceptor or mineralize RDX under these conditions. However, MJ1(T) transformed RDX into MNX, methylenedinitramine, formaldehyde, formate, ammonium, nitrous oxide, and nitrate. The nearest phylogenetic relative with a validly published name was Desulfotomaculum guttoideum (95 % similarity). However, MJ1(T) was also related to Clostridium celerecrescens DSM 5628 (95 %), Clostridium indolis DSM 755 (94 %), and Clostridium sphenoides DSM 632 (94 %). DNA:DNA hybridization with these strains was between 6.7 and 58.7 percent. The dominant cellular fatty acids (greater than 5 % of the total, which was 99.0 % recovery) were 16:0 fatty acid methyl ester (FAME) (32.12 %), 18:1cis 11 dimethyl acetal (DMA) (16.47 %), 16:1cis 9 DMA (10.28 %), 16:1cis 9 FAME (8.10 %), and 18:1cis 9 DMA (5.36 %). On the basis of morphological, physiological, and phylogenetic data, Clostridium geopurificans is proposed as a new species in genus Clostridium, with strain MJ1(T) as the type strain.
Keywords: NEUTRAL RED; MARINE SEDIMENT; BIODEGRADATION; PHYLOGENY; REDUCTION; OCTAHYDRO-1,3,5,7-TETRANITRO-1,3,5,7-TETRAZOCINE; HEXAHYDRO-1-NITROSO-3,5-DINITRO-1,3,5-TRIAZINE; ANTHRAQUINONE-2,6-DISULFONATE; MINERALIZATION; ACIDS